A SINTESIS KITOSAN DARI CANGKANG KERANG DARAH (Anadara granosa) SEBAGAI BIOSENSOR UNTUK DETEKSI PESTISIDA MENGGUNAKAN MEMBRAN Au/KITOSAN - Pharnanda, Rossella; Prasetya, Predian Yudha; Handayani, Suci Tri; Fatehah, Aura Amalia; Basukiwardojo, Maria Monica Sianita (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2024)
Pesticides are chemicals that can kill or control pests. However, the current use of pesticides poses a threat to humans and the environment. This research aims to develop a biosensor with Au/Chitosan membrane electrode using chitosan from blood clam shell waste which has high sensitivity to pesticides, fast response time, and long-term stability. So as to achieve the target of Sustainable Development Goals (SDG's) 3, namely health and well-being. The method used is the preparation of blood clam shells, synthesis of chitosan from blood clam shells, making Au/Chitosan membrane electrodes, characterisation of pesticide detection biosensors. The results of FTIR testing of chitosan obtained a degree of deacetylation of 86.3202%. The successfully made Au/Chitosan membrane electrode has an optimum concentration of 5% with the best measurement at pH 7, deposition time of 5 seconds, and scan rate of 0.1 V/s. Characterisation of carbamate pesticide detection biosensor using Au/Kitosan electrode shows that the Nernst factor obtained is 35.46 mV/decade, detection limit is 2x10 -8 M, measurement range is 10-8 M to 10-2 M, response time is 5-7 minutes, and precision with coefficient of variation for 10-4 M and 10-2 M concentration is 1.095% and 0.412% so that the Au/Chitosan membrane electrode can be used to detect carbamate pesticides effectively.